The Construction of Smoking Addiction Scale in Adolescents - Putra, Dwiki Nardian; Wakhidah, Sofiyyatuw; Briliani, Afifah Tiara; Pramesti, Afifah Dwi; Saputra, Anas Adha; Kusuma, Icha Putri; Husna, Aftina Nurul (Prosiding University Research Colloquium, 2021)
The purpose and benefits of this research is to develop an instrument used to measure psychological attributes and it is hoped that this scale can be used for further research. Addiction is a form of psychological dependence between a person and a stimulus, which is usually not always an object or substance. There are two aspects in this scale, namely the psychological aspect and the physical aspect. The stages of Scale Development start from setting the measurement objectives, confirming the measuring area, and psychometric testing. Furthermore, item writing includes the selection of the stimulus format, the selection of the response format, the writing of items: rules, item testing. Then the psychometric test. The subjects of this study consisted of 53 male adolescent respondents who smoked and were aged 13-19 years old, domiciled in the City/Regency of Magelang. The way to collect this research data is through an online survey. The results of the content validity test by referring to the Aiken’s V formula with a V value of 0.9, there are 9 items that are good because the results have reached 0.9. And as many as 20 items that must be revised because V is close to 0.9. Based on the results of the reliability test, Cronbach’s alpha was 0.957, which means the item is very good. The smoking addiction scale in adolescents was developed and produced 60 items, then a reliability test was carried out using SPSS statistic 22 software so that the final result of this scale was that there were 20 items that could represent the construct being measured.